Peran Nanoteknologi Dalam Peningkatan Nutrisi Tanah Dan Produktivitas Pertanian - * Yulianto (CV. SINAR HOWUHOWU, 2025)
Nanotechnology has emerged as a key innovation in modern agriculture due to its ability to enhance fertilizer efficiency, soil quality, and crop productivity. This study aims to evaluate the effects of nitrogen, phosphorus, and potassium nanoparticles on maize growth, soil nutrient content, and crop yield. The research employed an experimental approach using a Randomized Complete Block Design (RCBD) with three nanofertilizer treatments and a control. Results indicate that nanotechnology significantly increased plant height, leaf number, root length, biomass, and the protein and mineral content of maize grains. Additionally, soil quality improved in terms of nutrient availability, pH, and cation exchange capacity. Treated plants also exhibited greater resistance to environmental stress, while nanosensors supported precise and efficient agricultural management. This study confirms that nanotechnology has significant potential to enhance soil nutrition and crop productivity sustainably.